Composite core body with multi-layer gradient structure as well as preparation method and application of composite core body

By adopting a composite core with a multi-layer gradient structure, fiber combing and plasma pretreatment improve the hydrophilicity of the absorber layer, and forming a gradient pore structure through needle-punching and thermal bonding reinforcement, the existing composite core absorption is solved. The problem of SAP gel group formation after liquid has achieved rapid liquid absorption, anti-respiration and multiple liquid absorption.

CN119499042APending Publication Date: 2025-02-25HANGZHOU QIANZHIYA HYGIENE PRODUCTS CO LTD

Patent Information

Application Number
CN202411431592.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

After the existing composite core absorbs liquid, SAP is prone to form a large gel group, resulting in a decrease in the liquid absorption speed and the inability to absorb liquid multiple times. At the same time, there is a problem of SAP particles falling off.

Method used

The composite core adopts a multi-layer gradient structure, including a conductive layer, a flow guide layer and an absorbing layer, improves the hydrophilicity of the absorbing layer through fiber combing and plasma pretreatment, and forms a gradient through needle-punching composite and thermal bonding reinforcement methods. Pore ​​structure.

Benefits of technology

It achieves the effects of rapid liquid absorption, anti-respiration and multiple liquid absorption, avoids the fall of SAP particles, and improves the feel and wear comfort of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499042A_ABST
    Figure CN119499042A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite core body with a multi-layer gradient structure. The preparation method comprises the following steps: preparing a conducting layer by carding first fibers into a net; the diversion layer is prepared by carding a mixed raw material of 30-40% of SAF fibers and second fibers into a net; 50-60% of mixed raw materials of SAF fibers and third fibers are adopted and carded into a net, and the fiber net is subjected to disorder treatment through a high impurity roller to prepare the absorption layer; the diameter of the first fiber is larger than that of the second fiber; the conducting layer, the flow guide layer and the absorption layer are laminated and combined from top to bottom and then are compounded into an integrated structure core body by adopting a mechanical reinforcement, chemical reinforcement or thermal bonding reinforcement method; and the SAF fibers in the absorption layer are pretreated by adopting plasma. The composite core body adopts the full-fiber absorption layer, so that the granular sensation is reduced and the hand feeling is improved; needling compounding is adopted, a three-dimensional net-shaped structure is formed among all the layers, the flow guide and absorption speed is increased, and the modified SAF fibers can effectively lock moisture and reduce back seepage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of disposable absorbent products, and in particular relates to a composite core body with a multi-layer gradient structure and a preparation method and application thereof. Background Art

[0002] The absorbent core is the core component of disposable absorbent products, especially diapers, sanitary napkins, pull-up pants, adult care pants and other sanitary products. The performance of disposable absorbent products is mainly determined by the absorbent core. The process development of the absorbent core has gone through several stages. The first generation of cores is formed by mixing fluff pulp and SAP and forming in one step. The second generation of cores was improved on the basis of the first generation. It is made of dust-free paper, fluff pulp and SAP bonding and compounding. It is lighter and more breathable. The third generation of cores is formed by mixing hot melt adhesive, non-woven fabric and SAP. It does not clump after absorbing moisture and can maintain its original shape. However, at present, the third generation of composite cores is easy to form large gel groups after absorbing liquid, which reduces the multiple liquid absorption capacity and liquid absorption rate of diapers. In order to improve the liquid absorption rate, anti-re-seepage performance and multiple liquid absorption of disposable absorbent products, it is very necessary to design a suitable composite absorbent core. Summary of the invention

[0003] In order to solve one of the above problems, the present invention provides a composite core with a multi-layer gradient structure and a preparation method and application thereof.

[0004] In order to achieve the above object, the present invention adopts the following technical means:

[0005] A first aspect of the present invention provides a method for preparing a composite core with a multi-layer gradient structure, wherein the composite core comprises a conductive layer, a flow-guiding layer and an absorption layer, and the preparation method comprises the following steps:

[0006] The conductive layer is prepared by combing the first fiber into a web;

[0007] The guide layer is made of a mixed raw material of 30-40% SAF fiber and second fiber, which is carded into a web;

[0008] The absorption layer is made of a mixed raw material of 50-60% SAF fiber and a third fiber, which is combed into a web and then subjected to a high-mix roller to perform a random treatment on the fiber web.

[0009] The diameter of the first fiber is greater than the diameter of the second fiber and greater than the diameter of the third fiber;

[0010] The conductive layer, the guide layer and the absorbent layer are laminated from top to bottom and then composited into an integrated structural core by mechanical reinforcement, chemical reinforcement or thermal bonding reinforcement method;

[0011] The SAF fibers in the absorbent layer are pretreated with plasma.

[0012] In some embodiments of the present invention, the plasma pretreatment process is: using air as the treatment gas under normal pressure, discharging for 10-20 seconds and stopping for 3-5 seconds, the total treatment time is 45-50 seconds, and the treatment power is 100-200w.

[0013] In some embodiments of the present invention, a layer of dust-free paper is further provided on the conductive layer, and a concave-convex pattern is pressed out on the dust-free paper by a pressing roller. The embossing not only allows the core to meet different appearance requirements and increase the aesthetics, but the concave-convex pattern thereon also has the function of guiding flow, thereby enhancing the absorption performance of the core and maintaining a dry and cool surface experience.

[0014] In some embodiments of the present invention, the first fiber, the second fiber, and the third fiber are one of cotton fiber, viscose fiber, polyester fiber, polypropylene fiber, or fluff pulp fiber.

[0015] In some embodiments of the present invention, the third fiber is a mixture of two of cotton fiber, viscose fiber, polyester fiber, polypropylene fiber or fluff pulp fiber.

[0016] In some embodiments of the present invention, the mechanical reinforcement adopts a needle punching composite: vertical needles and oblique needles are staggered, and the needle punching density is 3-6 needles / cm 2 The inclination angle of the oblique needle is 15°-45°; in some embodiments of the present invention, the chemical reinforcement adopts adhesive bonding; in some embodiments of the present invention, the thermal bonding reinforcement adopts hot air compounding.

[0017] In some embodiments of the present invention, a layer of porous foam material is further disposed under the absorbent layer.

[0018] In some embodiments of the present invention, the porous foam material is a polyurethane foam material, and the thickness of the material is 0.1-0.5 mm.

[0019] The second aspect of the present invention provides a composite core prepared by the method described in the first aspect.

[0020] The third aspect of the present invention provides the use of the composite core described in the second aspect in disposable care products and medical dressings.

[0021] Beneficial effects of the present invention

[0022] Compared with the prior art, the present invention has the following beneficial effects: the present invention provides a composite core with a multi-layer gradient structure, which adopts a full-fiber absorption layer and does not use traditional SAP particles. This can solve the problem that SAP easily forms larger gel groups after the composite core absorbs liquid, the liquid absorption speed is reduced, and the liquid cannot be absorbed multiple times. There is no risk of SAP particles falling onto the surface of disposable care products. At the same time, it can also effectively reduce the granularity caused by SAP and improve the feel of the product.

[0023] The conductive layer, the guide layer and the absorption layer of the present invention respectively use fibers of different finenesses, and the porosity and pore size formed after reinforcement change in a gradient. At the same time, when the three layers are compounded, a needle-punched compound method is adopted to increase the three-dimensional network structure between the layers in the longitudinal direction, provide a transportation channel for the diversion and diffusion of the liquid, which is beneficial to the downward transmission of the liquid, and can make the liquid quickly conduct without liquid accumulation, thereby improving the diversion and absorption speed. The SAF fiber of the absorption layer is treated with plasma to increase the hydrophilicity of the fiber. While absorbing the liquid, it can also effectively lock in moisture and reduce re-seepage.

[0024] A porous foam material layer is added under the absorption layer. The porous foam material layer is stretchable and breathable, so that the core body will not fold, and displacement and pinching of the buttocks during use can be avoided. During use, the disposable care products can maintain a good shape, increase the comfort of wearing, and reduce the stuffiness caused by the transitional fit between the disposable absorbent products and the skin. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The comparison of hydrophilicity of SAF fibers treated with plasma for different time periods in the present invention is shown;

[0026] Figure 2 The figure shows the comparison of the absorption speed of the composite core of the present invention under different needling combinations. DETAILED DESCRIPTION

[0027] The following examples are used to demonstrate preferred embodiments of the present invention. It will be appreciated by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors that can be used to implement the present invention and therefore can be considered as preferred embodiments of the present invention. However, it will be appreciated by those skilled in the art based on this specification that many modifications may be made to the specific embodiments disclosed herein and still achieve the same or similar results without departing from the spirit or scope of the present invention.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs, and the materials cited herein and those cited by them are incorporated by reference. Those skilled in the art will recognize or will learn through routine experimentation that there are many equivalents to the specific embodiments of the invention described herein. Such equivalents are intended to be encompassed by the claims.

[0029] The present invention provides a method for preparing a composite core with a multi-layer gradient structure, wherein the composite core comprises a conductive layer, a flow-guiding layer and an absorption layer, and the preparation method comprises the following steps:

[0030] The conductive layer is prepared by combing the first fiber into a web;

[0031] The guide layer is made of a mixed raw material of 30-40% SAF fiber and second fiber, which is carded into a web;

[0032] The absorption layer is made of a mixed raw material of 50-60% SAF fiber and the third fiber, which is carded into a web and then processed by a high-mix roller to make the fiber web messy.

[0033] The diameter of the first fiber is greater than the diameter of the second fiber which is greater than the diameter of the third fiber;

[0034] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then compounded into an integrated structural core by needle punching; the needle punching compound adopts the form of vertical needles and oblique needles staggered, and the needle punching density is 3-6 needles / cm 2 ; The inclination angle of the oblique needle is 15°-45°, preferably 30°.

[0035] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 10-20s and stopped for 3-5s, the total treatment time is 45-50s, and the treatment power is 100-200w.

[0036] The first fiber, the second fiber and the third fiber are one of cotton fiber, viscose fiber, polyester fiber, polypropylene fiber or fluff pulp fiber; the third fiber can also be a mixture of two of cotton fiber, viscose fiber, polyester fiber, polypropylene fiber or fluff pulp fiber.

[0037] As another improvement of the present invention, a layer of dust-free paper is further arranged on the conductive layer.

[0038] As another improvement of the present invention, a layer of porous foam material is further provided under the absorption layer; the porous foam material is polyurethane foam material, and the thickness of the material is 0.1-0.5 mm.

[0039] The present invention provides a composite core prepared by the above method and the application of the composite core in disposable care products and medical dressings. Disposable care products include sanitary napkins, pet care pads, diapers, pull-up pants, nursing pants, menstrual pants and other disposable products.

[0040] The preparation of gradient structure composite structure has a wide range of raw material choices. According to the performance requirements of the product, the surface density and thickness of the conductive layer, the guide layer and the absorption layer as well as the fiber raw materials can be adjusted to achieve the effect of adjusting the liquid absorption amount, re-infiltration and absorption speed, and has good process flexibility.

[0041] The technical solution of this patent is further described in detail below in conjunction with specific implementation methods but is not intended to limit the content of patent protection.

[0042] Example 1

[0043] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorption layer, and a preparation method comprising the following steps:

[0044] The conductive layer is made of 30 micron diameter cotton fibers carded into a web;

[0045] The guide layer is made of a mixed raw material of 30% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0046] The absorbent layer is made of a mixture of 50% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the web messy.

[0047] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then acupunctured to form an integrated structural core; the acupuncture compound adopts the form of vertical needles and oblique needles interlaced, and the acupuncture density is 4 needles / cm 2 ; The inclination angle of the oblique needle is 30°.

[0048] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 50 seconds, and the treatment power is 100W.

[0049] Example 2

[0050] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorption layer, and a preparation method comprising the following steps:

[0051] The conductive layer is made of 30 micron diameter cotton fibers carded into a web;

[0052] The guide layer is made of a mixed raw material of 35% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0053] The absorbent layer is made of a mixture of 55% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the web messy.

[0054] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then acupunctured to form an integrated structural core; the acupuncture compound adopts the form of vertical needles and oblique needles interlaced, and the acupuncture density is 4 needles / cm 2 ; The inclination angle of the oblique needle is 30°.

[0055] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 50 seconds, and the treatment power is 100W.

[0056] Example 3

[0057] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorption layer, and a preparation method comprising the following steps:

[0058] The conductive layer is made of 30 micron diameter cotton fibers carded into a web;

[0059] The guide layer is made of a mixed raw material of 40% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0060] The absorbent layer is made of a mixture of 60% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the web messy.

[0061] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then acupunctured to form an integrated structural core; the acupuncture compound adopts the form of vertical needles and oblique needles interlaced, and the acupuncture density is 4 needles / cm 2 ; The inclination angle of the oblique needle is 30°.

[0062] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 50 seconds, and the treatment power is 100W.

[0063] Example 4

[0064] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorption layer, and a preparation method comprising the following steps:

[0065] The conductive layer is made of 30 micron diameter cotton fibers carded into a web;

[0066] The guide layer is made of a mixed raw material of 30% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0067] The absorbent layer is made of a mixture of 50% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the web messy.

[0068] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then acupunctured to form an integrated structural core; the acupuncture compound adopts the form of vertical needles and oblique needles interlaced, and the acupuncture density is 4 needles / cm 2 ; The inclination angle of the oblique needle is 30°.

[0069] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 75 seconds, and the treatment power is 100W.

[0070] Example 5

[0071] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorption layer, and a preparation method comprising the following steps:

[0072] The conductive layer is made of 30 micron diameter cotton fibers carded into a web;

[0073] The guide layer is made of a mixed raw material of 30% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0074] The absorbent layer is made of a mixture of 50% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the web messy.

[0075] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then acupunctured to form an integrated structural core; the acupuncture compound adopts the form of vertical needles and oblique needles interlaced, and the acupuncture density is 4 needles / cm 2 ; The inclination angle of the oblique needle is 30°.

[0076] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 125 seconds, and the treatment power is 100W.

[0077] Example 6

[0078] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorption layer, and a preparation method comprising the following steps:

[0079] The conductive layer is made of 40 micron diameter fluff pulp fibers carded into a web;

[0080] The guide layer is made of a mixed raw material of 30% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0081] The absorbent layer is made of a mixture of 50% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the web messy.

[0082] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then compounded into an integrated structural core by needle punching; the needle punching compound adopts the form of straight needles, and the needle punching density is 4 needles / cm 2 .

[0083] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 50 seconds, and the treatment power is 100W.

[0084] Example 7

[0085] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorption layer, and a preparation method comprising the following steps:

[0086] The conductive layer is made of 40 micron diameter fluff pulp fibers carded into a web;

[0087] The guide layer is made of a mixed raw material of 30% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0088] The absorbent layer is made of a mixture of 50% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the web messy.

[0089] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then compounded into an integrated structural core by needle punching; the needle punching compound adopts the form of vertical needles and oblique needles, and the needle punching density is 4 needles / cm 2 , the inclination angle of the oblique needle is 30°.

[0090] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 50 seconds, and the treatment power is 100W.

[0091] Example 8

[0092] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorption layer, and a preparation method comprising the following steps:

[0093] The conductive layer is made of 30 micron diameter cotton fibers carded into a web;

[0094] The guide layer is made of a mixed raw material of 35% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0095] The absorbent layer is made of a mixture of 55% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the web messy.

[0096] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then composited into an integrated structural core using hot air.

[0097] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 50 seconds, and the treatment power is 100W.

[0098] Example 9

[0099] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer, and an absorbing layer;

[0100] The conductive layer is made of 30 micron diameter cotton fibers carded into a web;

[0101] The guide layer is made of a mixed raw material of 30% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0102] The absorption layer is made of a mixed raw material of 50% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the fiber web messy.

[0103] The conductive layer, the guide layer, and the absorbent layer are stacked from top to bottom and then compounded into an integrated structural core using a chemical adhesive method; the adhesive coating amount is 0.2g / cm 2 .

[0104] Then a layer of dust-free paper is compounded on the composite core, and a concave-convex pattern is pressed on the dust-free paper by a pressing roller.

[0105] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 50 seconds, and the treatment power is 100W.

[0106] Example 10

[0107] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer, and an absorbing layer;

[0108] The conductive layer is made of 30 micron diameter cotton fibers carded into a web;

[0109] The guide layer is made of a mixed raw material of 30% SAF fiber and 20 micron diameter viscose fiber, which is carded into a web;

[0110] The absorption layer is made of a mixed raw material of 50% SAF fiber and 10 micron diameter viscose fiber, which is carded into a web and then processed by a high-mix roller to make the fiber web messy.

[0111] The conductive layer, the guide layer, and the absorbent layer are stacked from top to bottom and then compounded into an integrated structural core by needle punching; the needle punching compound adopts the form of vertical needles and oblique needles staggered, and the needle punching density is 4 needles / cm 2 ; The inclination angle of the oblique needle is 30°.

[0112] Then a support layer is compounded under the composite core, and the support layer is prepared by foaming polyurethane material with a thickness of 0.3 mm.

[0113] The SAF fibers in the absorption layer are pretreated with plasma; the plasma pretreatment process is: air is used as the treatment gas under normal pressure, each discharge is 20 seconds and the rest is 5 seconds, the total treatment time is 50 seconds, and the treatment power is 100W.

[0114] Embodiment 11

[0115] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorbing layer;

[0116] The conductive layer is made of cotton fibers combed into a web;

[0117] The guide layer is made of a mixed raw material of 35% SAF fiber and viscose fiber, which is carded into a web;

[0118] The absorption layer is made of a mixture of 55% SAF fiber and viscose fiber, which is combed into a web and then processed by a high-mix roller. The fiber diameters in the conductive layer, the guide layer and the absorption layer are consistent, which is 15 microns.

[0119] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then punched vertically to form an integrated structural core.

[0120] Example 12

[0121] A composite core with a multi-layer gradient structure, the composite core comprising a conductive layer, a flow-guiding layer and an absorbing layer;

[0122] The conductive layer is made of cotton fibers combed into a web;

[0123] The guide layer is made of a mixed raw material of 35% SAF fiber and viscose fiber, which is carded into a web;

[0124] The absorption layer is made of a mixture of 55% SAF fiber and viscose fiber, which is combed into a web and then processed by a high-mix roller. The fiber diameters in the conductive layer, the guide layer and the absorption layer are consistent, which is 15 microns.

[0125] The conductive layer, the guide layer and the absorbent layer are stacked from top to bottom and then composited into an integrated structural core using hot air.

[0126] (1) The water absorption of untreated SAF fibers, plasma-treated SAF fibers in Example 1, Example 4 and Example 5 was tested: fiber samples of equal mass were placed in an environment with a humidity of 60% and a temperature of 22°C for 24 hours, and the mass change rate of the fiber samples before and after the experiment was measured. The results are shown in FIG. Figure 1 shown.

[0127] The results show that the hydrophilicity of SAF fibers increases after being treated with plasma for about 50 seconds. When the plasma treatment time of SAF fibers is too long, the degree of fiber etching increases and the hydrophilicity weakens.

[0128] (2) When preparing the core in Example 1, straight needles, 15° oblique needles, 30° oblique needles, 45° oblique needles, and 60° oblique needles were used to prepare the cores respectively, and the absorption speed of the prepared different cores was measured. The results are as follows: Figure 2 shown.

[0129] The results showed that the combination of straight and oblique needles could help improve the absorption rate, but the oblique needle angle should not exceed 45°.

[0130] (3) The composite cores prepared in Examples 1 to 10 were tested for absorption performance using an absorption rate measuring instrument, and the data were recorded. The results of the effects of the composite core structure on the absorption performance in each example are shown in Table 1:

[0131] Table 1 Water absorption and back-infiltration performance of composite core

[0132]

[0133] The comparison results of the above embodiments show that the composite core obtained by needle-punching the conductive layer, the guide layer and the absorbent layer prepared by using cellulose with gradually decreasing diameters has significant advantages in absorption speed and re-permeability performance compared with fibers with the same diameter.

[0134] In the composite process of the core, compared with hot air composite, the composite core of needle-punched composite has significant advantages in absorption speed and re-permeability.

[0135] In the acupuncture composite process, the absorbent core prepared by straight needle composite has a slight advantage in absorption speed over the absorbent core prepared by the combination of vertical needle and oblique needle composite. The oblique needle can further improve the liquid absorption speed of the core. This may be because the oblique needle composite forms an inclined channel between the composite layers, which helps to transport the liquid to the surrounding area for absorption.

[0136] Compared with unmodified SAF fibers, the modified SAF fibers have increased hydrophilicity and liquid absorption speed after plasma modification, and the anti-re-seepage performance does not decrease; however, the plasma modification time of SAF fibers should not be too long. Too long plasma treatment will cause excessive etching of SAF fibers, resulting in poor hydrophilicity of SAF fibers, slowed second absorption speed, and reduced anti-re-seepage performance. The plasma treatment time of SAF fibers is preferably 45-50S.

[0137] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as references separately. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined in the present application.

Claims

1. A method for preparing a composite core with a multi-layer gradient structure, characterized in that: The composite core comprises a conductive layer, a flow-guiding layer and an absorbing layer, and the preparation method comprises the following steps: The conductive layer is prepared by combing the first fiber into a web; The guide layer is made of a mixed raw material of 30-40% SAF fiber and second fiber, which is carded into a web; The absorption layer is made of a mixed raw material of 50-60% SAF fiber and a third fiber, which is combed into a web and then subjected to a high-mix roller to perform a random treatment on the fiber web. The diameter of the first fiber is greater than the diameter of the second fiber and greater than the diameter of the third fiber; The conductive layer, the guide layer and the absorbent layer are laminated from top to bottom and then composited into an integrated structural core by mechanical reinforcement, chemical reinforcement or thermal bonding reinforcement method; The SAF fibers in the absorbent layer are pretreated with plasma.

2. The method for preparing a composite core with a multi-layer gradient structure according to claim 1, characterized in that: The plasma pretreatment process is: using air as the treatment gas under normal pressure, discharging for 10-20 seconds and stopping for 3-5 seconds, the total treatment time is 45-50 seconds, and the treatment power is 100-200w.

3. The method for preparing a composite core with a multi-layer gradient structure according to claim 1, characterized in that: A layer of dust-free paper is also arranged on the conductive layer.

4. The method for preparing a composite core with a multi-layer gradient structure according to claim 1, characterized in that: The first fiber, the second fiber and the third fiber are one of cotton fiber, viscose fiber, polyester fiber, polypropylene fiber or fluff pulp fiber.

5. The method for preparing a composite core with a multi-layer gradient structure according to claim 4, characterized in that: The third fiber is a mixture of two of cotton fiber, viscose fiber, polyester fiber, polypropylene fiber or fluff pulp fiber.

6. The method for preparing a composite core with a multi-layer gradient structure according to claim 1, characterized in that: The mechanical reinforcement adopts acupuncture compound: vertical needles and oblique needles are staggered, and the acupuncture density is 3-6 needles / cm 2 , the inclination angle of the oblique needle is 15°-45°.

7. The method for preparing a multi-layer gradient-bonded composite core according to claim 1, characterized in that: A layer of porous foam material is also arranged under the absorption layer.

8. The method for preparing a multi-layer gradient-bonded composite core according to claim 7, characterized in that: The porous foam material is a polyurethane foam material, and the thickness of the material is 0.1-0.5 mm.

9. A composite core prepared according to the method according to any one of claims 1 to 8.

10. Use of the composite core according to claim 9 in disposable care products and medical dressings.

Citation Information

Patent Citations

  • Pretreatment process for spinning of kapok loose fibers

    CN103451911A

  • Absorbent core for disposable absorbent articles

    CN103596535A

  • Preparation method of antimicrobial excipient

    CN109577018A

  • Absorption article with novel structure

    CN110638578A

  • Super-absorbent fiber multi-layer gradient structure absorbent core layer

    CN111568645A

Cited By

  • Multifunctional VAE composite wear-resistant nursing pad and preparation method thereof

    CN120392424A

  • Nursing pad with gradient absorption structure and compounding process thereof

    CN120549704A